The quantitative enamel firing technique based on regression analysis. - Yaqin Qian; Xiangdong Dai (PLoS ONE)
Enamel firing, as a key technique of enamel craftsmanship, has had no quantitative standards to follow since ancient times. To solve this problem, linear regression analysis was used to conduct quantitative enamel firing experiments. Through enamel firing experiments on enamel specimens with different masses, the linear regression equation was solved using the obtained experimental data and the regression equation was subjected to the analysis of variance. The experimental results indicate that the mass of enamel specimens has a real linear regression relationship with the firing duration. To verify the applicability of the linear regression equation, the equation was applied and validated. That is, enamel specimens with different specifications and colors were prepared, the firing durations of which were then calculated using the regression equation. The enamel specimens were fired according to the calculated firing durations, all obtaining optimal enamel decorations. The following conclusions are drawn: simulating enamel firing using the linear regression equation established in the quantitative enamel firing experiments can realize a quantitative, standardized enamel firing technique.